F1 Domain of the Leishmania (Leishmania) donovani Nucleoside Hydrolase Promotes a Th1 Response in Leishmania (Leishmania) infantum Cured Patients and in Asymptomatic Individuals Living in an Endemic Area of Leishmaniasis - Carrillo, Eugenia; Fernandez, Laura; Ibarra-Meneses, Ana Victoria; Santos, Micheli L. B.; Nico, Dirlei; de Luca, Paula M.; Correa, Cristiane Bani; de Almeida, Roque Pacheco; Moreno, Javier; Palatnik-de-Sousa, Clarisa B. (Frontiers in Immunology, 2017)
The Leishmania (Leishmania) donovani nucleoside hydrolase NH36 is the main antigen of the Leishmune® vaccine and one of the promising candidates for vaccination against visceral leishmaniasis. The antigenicity of the N-terminal (F1), the central (F2) or the C-terminal recombinant domain (F3) of NH36 was evaluated using PBMC from individuals infected with L. (L.) infantum from an endemic area of visceral leishmaniasis of Spain. Both NH36 and F1 domain significantly increased the PBMC proliferation stimulation index of cured patients and infected asymptomatic individuals compared to healthy controls. Moreover, F1 induced a 19 % higher proliferative response than NH36, in asymptomatic exposed subjects. Additionally, in patients cured from visceral leishmaniasis, proliferation in response to NH36 and F1 was accompanied by a significant increase of IFN- and TNF-α secretion, which was 42-43% higher, in response to F1 than to NH36. The IL-17 secretion was stronger in asymptomatic subjects, In response to F1, as well as in cured cutaneous leishmaniasis after NH36 stimulation. While no IL-10 secretion was determined by F1, a Granzyme B increase was detected in supernatants from cured patients after stimulation with either NH36 or F1. These data demonstrate that F1 is the domain of NH36 that induces a recall cellular response in individuals with acquired resistance to the infection by L. (L.) infantum. Additionally, F1 and NH36 discriminated the IgG3 humoral response in patients with active visceral leishmaniasis due to L. (L.) donovani (Ethiopia) and L. (L.) infantum (Spain), from that of endemic and non-endemic area controls. NH36 showed higher reactivity with sera from L. (L.) donovani-infected individuals, indicating species-specificity. We conclude that, the F1 domain, previously characterized as an inducer of the Th1 and Th17 response in cured/exposed patients infected with L. (L.) infantum chagasi, may be also involved in generation of a protective response against Leishmania (L.) infantum and represents a potential vaccine candidate for the control of human leishmaniasis alone, or in combination with other HLA epitopes/antigens.